2019
DOI: 10.1017/s0967199419000030
|View full text |Cite
|
Sign up to set email alerts
|

What are the effects of vitamin C on sperm functional properties during direct swim-up procedure?

Abstract: SummaryDirect swim-up procedure is widely used to separate the motile competent spermatozoa from the antioxidant-rich semen. Subsequently, spermatozoa become more vulnerable to reactive oxygen species (ROS) due to their cytological characteristics. The effect of vitamin C, a highly concentrated antioxidant in the semen, on direct swim-up-enriched sperm population is not fully investigated. Therefore, the aim of the present study was to assess the effect of vitamin C on sperm functional properties during direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 57 publications
2
22
0
Order By: Relevance
“…This process can lead to damages to polyunsaturated lipids present in sperm plasma membrane, as well as to the DNA, RNA and proteins (Atig, Kerkeni, Saad, & Ajina, ; Kamkar, Ramezanali, & Sabbaghian, ; Mello Filho et al, ; Sposito et al, ). This imbalance can also be observed in reproductive biotechnologies, (e.g., semen cryopreservation; Amidi, Pazhohan, Shabani, Khodarahmian, & Nekoonam, ; Panner Selvam et al, ), in vitro fertilisation and in protocols with an excessive manipulation of semen, as plasma separation through centrifugation (Donnelly et al, ) and also sperm separation (Raad et al, ). However ROS, under physiological conditions, are important to many process can occur, such as events involving reproductive process, like sperm capacitation, hypermotility, cellular activation, interaction with zona pellucida and acrosome reaction (Banihani et al, ; Moretti et al, ; Satorre et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This process can lead to damages to polyunsaturated lipids present in sperm plasma membrane, as well as to the DNA, RNA and proteins (Atig, Kerkeni, Saad, & Ajina, ; Kamkar, Ramezanali, & Sabbaghian, ; Mello Filho et al, ; Sposito et al, ). This imbalance can also be observed in reproductive biotechnologies, (e.g., semen cryopreservation; Amidi, Pazhohan, Shabani, Khodarahmian, & Nekoonam, ; Panner Selvam et al, ), in vitro fertilisation and in protocols with an excessive manipulation of semen, as plasma separation through centrifugation (Donnelly et al, ) and also sperm separation (Raad et al, ). However ROS, under physiological conditions, are important to many process can occur, such as events involving reproductive process, like sperm capacitation, hypermotility, cellular activation, interaction with zona pellucida and acrosome reaction (Banihani et al, ; Moretti et al, ; Satorre et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Most reports describe that antioxidant supplementation in semen may improve the oxidative equilibrium (Bousnane, May, Yahia, & Abu‐Alhaija, ). This has been attempted during cryopreservation (Panner Selvam, Henkel, Sharma, & Agarwal, ; Satorre, Breininger, & Beconi, ), in vitro fertilisation (Griveau & Le Lannou, ) and semen processing (Hughes, Lewis, McKelvey‐Martin, & Thompson, ; Raad et al, ), to name a few. Moreover, semen processing by density gradient centrifugation, which is commonly used in assisted reproduction technologies (Harlev, Henkel, Samanta, & Agarwal, ; Inoue et al, ; Walters et al, ), has a demonstrated capacity to lead to sperm oxidative damage (Aitken & Clarkson, ; Henkel & Schill, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular vitamin C and vitamin E are of interest because the body cannot synthesize them and therefore systemic concentrations directly relate to dietary intake [59,60]. Previous increased dietary intake of vitamin C in men reduced sperm oxidative DNA damage (8OHdG) [61], while in vitro exposure of sperm to 300 µM of ascorbic acid (the active component of vitamin C) had beneficial effects on sperm intracellular ROS levels and sperm chromatin integrity [62]. The same has also been shown for vitamin E both in vitro for protecting human sperm from induced oxidative stress at 40 μmol 1-1 vitamin E [63], and through oral supplementation of sub-fertile men to reduce sperm DNA fragmentation and oxidative stress [37].…”
Section: Discussionmentioning
confidence: 99%
“…The average age of first-time fathers is increasing worldwide. In the past 60 years in Australia, the median age of fathers has increased from 29.0 years to now 33.1 years (~15%) [1], with 10% of all naturally conceived births now coming from fathers ≥40 years [2]. These statistics are heightened within couples seeking assisted reproductive technology (ART) treatment, due to the strong relationship between paternal age and sub-fertility [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%